Avaliação de sistemas de desfluoretação de águas para comunidades rurais do semi-árido - Lima Júnior, José Ferreira (2012)
This research was undertaken to evaluate, implement and compare the effectiveness of two water defluoridation systems in two locations with endemic fluorosis problem in the countryside of São João do Rio do Peixe, Paraiba. The systems investigated were the Water Treatment Resort (ETA) and Defluoridation Regenerable Filter (DRF). The study was divided into two parts, namely: Part I (risk assessment: mapping of residual levels of fluoride in groundwater and perception of dental fluorosis) and Part II (reduction of injuries: defluoridation systems). The sample consisted of 59 individuals of both sexes and different age groups, being 29 for the study of ETA (artesian well with 5.3 mg/L fluoride) and 30 for the FDR (artesian well with 2.6 mg/L fluoride). To investigate the estimation of fluoride intake were collecting water, other liquids, by food duplicate plate methodology. For children the estimated intakes of fluoride dentifrice was performed with a simulated toothbrushing. The excretion values of fluoride were estimated by collecting 24-hour urine. All samples were stored under refrigeration and analyzed for fluoride ion-selective electrode through direct and indirect method for diffusion hexamethyldisiloxane as appropriate. Evaluations were performed at two different times D1 (baseline) and D2 (1 to 2 months after defluoridation) for both defluoridation models (ETA and DRF). It was observed that the total fluoride intake and excretion decreased after installation of the two defluoridation models, both communitarian model (ETA) as the domiciliary model (FDR), thus indicating the effectiveness of these models to control optimal levels of fluoride in drinking water. The map of fluoride concentration in water from artesian wells in rural areas of São João do Rio do Peixe PB, confirmed the risk of dental fluorosis in that municipality. 63.9% of samples analyzed had [F] above the ideal value of 0.7 mg / L and 35% had values above 1.5 mg / L. It was estimated that about 2,465 people are at risk of developing dental fluorosis and 1,057 individuals can be affected by skeletal fluorosis. The water component of the diet was the largest contributor to total daily fluoride ingestion (50%) in two locations. It was observed that there was significant reduction in total fluoride intake in the group of children between periods D1-ETA (0.10 mg F / kg / day) for D2-ETA (0.04 mg F / kg / day) and D1-F (0.07 mg F / kg / day) for D2-F (0.03 mg F / kg / day) as well as for adult groups of ETA and the DRF. The period of regeneration in the ETA system was superior to DRF suggesting the application of the ETA system in locations with high concentrations of fluoride where FDR would not be effective (> 3.0 mg / L). It is concluded that the two defluoridation models were effective in reducing the intake of fluoride and therefore reducing the risk of dental fluorosis. Although both systems are effective in reducing the bioavailability of fluoride among users, only communitarian defluoridation system (ETA) has proved suitable for locations with high concentrations of fluoride at risk for skeletal fluorosis.